Synthesis and Characterization of Cellulose from Green Bamboo by Chemical Treatment with Mechanical Process - Liew, Fui Kiew; Sinin, Hamdan; Md. Rezaur, Rahman; Mohamad, Rusop; Josephine, Chang Hui Lai; Md. Faruk, Hossen; Md. Mizanur, Rahman (Hindawi Publishing Corporation, 2015)
Bamboo cellulose was prepared by chemical process involving dewaxing, delignification, and mercerization process. Four samples namely, green bamboo fiber (GBF), dewaxed bamboo fiber (DBF), delignified bamboo fiber (DLBF), and cellulose fiber (CF) had been analysed. FTIR and TGA analysis confirmed the removal of hemicellulose and lignin at the end stage of the process. FTIR results reveal that the D-cellulose OH group occurred at 1639 cm−1 region. SEM micrograph showed that mercerization leads to fibrillation and breakage of the fiber into smaller pieces which promote the effective surface area available for contact. Barrer, Joiyner, and Halenda (BJH) method confirmed that the effective surface area of CF is two times larger compared to GBF. CF showed the highest activation energy compared to GBF. It indicates that CF was thermally stable.